2021
DOI: 10.3390/socsci10090321
|View full text |Cite
|
Sign up to set email alerts
|

Are Working Children in Developing Countries Hidden Victims of Pandemics?

Abstract: The consequences of the recent pandemic have been disproportionately disruptive to several social groups, including children. As developing economies have been firefighting the recent pandemic, the welfare of minors could be affected and children’s economic exploitation and abuse could increase. Therefore, the present research aims to shed light on and to investigate the association between child labour in developing countries and pandemics, including the coronavirus, through conducting a systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 151 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…The Alliance for Child Protection in Humanitarian Action ( 20 ), Ahad et al ( 22 ), ILO ( 36 ), Mutashar et al ( 42 ), Kechagia and Metaxas ( 57 ), and Tran and Journal ( 60 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Alliance for Child Protection in Humanitarian Action ( 20 ), Ahad et al ( 22 ), ILO ( 36 ), Mutashar et al ( 42 ), Kechagia and Metaxas ( 57 ), and Tran and Journal ( 60 )…”
Section: Resultsmentioning
confidence: 99%
“…Various studies identified the need for civil society leaders and organizations to support the efforts of governments and businesses in fighting child labor. A number of reviewed studies recommended the need for civil society to work toward raising public awareness on the effects of child labor ( 20 , 22 , 36 , 42 , 57 , 60 ) ( Table 2 ). Moreover, two studies have stressed the need for donors such as international donor agencies – such as World Bank, USAID, ILO, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bissel (2020), the limits of child abuse include (a) working full time at an early age; (b) work that causes physical, social, and psychological stress; (c) insufficient wages and too many responsibilities; and (d) work that degrades the dignity of the child. Economic reasons cause children to work, as a result, the welfare of minors can be affected and exploitation and economic abuse of children can increase (Kechagia and Metaxas, 2021).…”
Section: Understanding Child Violence In Anomie Groupsmentioning
confidence: 99%
“…For example, from a policy perspective, there is a perception that the benefits of eliminating child labor worldwide are enormous [1]. In recent decades, there has been a notable commitment by international organisations to safeguard the rights of children and combat the issue of child labour [2]. The issue of child labour is frequently seen as a significant concern in numerous developing nations (see Kamruzzaman & Hakim,[3]; Öncü et al, [4]).…”
Section: Introductionmentioning
confidence: 99%